Synthesis of carbon materials by solution plasma reactor with stable discharge and advanced plasma spray deposition method. (4th March 2018) - Kum, Dae Sub; Park, Choon-Sang; Kim, Hyun-Jin; Shin, Jun-Goo; Kim, Dong Ha; Kim, Daseulbi; Bae, Gyu Tae; Kim, Jae Young; Cho, Byung-Kwon; Shin, Bhum Jae; Lee, Dong Ho; Chien, Sung-Il; et al.
ABSTRACT: This work presents a deposition of carbon thin films on the substrate from sucrose-containing-carbon source, that is, sugar, by using the two different plasma processes; one process is that the carbon particles are obtained from the sugar in the stable solution plasma reactor with external resistor, and the other process is that the carbon thin films are deposited on the substrate from the carbon particles obtained from sugar by using the atmospheric pressure plasma (APP) spray method. The carbon particles are obtained at a bipolar pulse waveform with a peak value of 1.5 kV and a frequency of 5 kHz under solution plasma, whereas the carbon thin films are deposited at a sinusoidal pulse waveform with a peak value of 12.5 kV and a frequency of 33 kHz under the APP spray method. Voltage probe, discharge current, and optical emission spectrometer (OES) techniques are used to analyze the plasma produced from the solution plasma reactor. Field emission scanning electron microscopy (FE-SEM) and ultraviolet–visible (UV-vis) spectroscopy techniques are used to analyze the carbon particles. FE-SEM results show that carbon materials from sucrose have a few ten to hundred nanometer size nanoparticles characteristics. The UV-vis and OES analyses show the characteristic graphene peaks with evidence that carbon sources from sucrose are broken due to discharge energy. This study contributes to a better understanding on the new synthesis method of carbon materials from renewable resource with low-cost, i.e . sugar cane.